Antibacterial Effect of Moringa oleifera Leaves on Staphylococcus aureus Based on Different Concentration and Harvest Time - Panjaitan, Jeremia Aris; Kusumawati, R. Lia; Yunanda, Yuki; Lubis, Arvitamuriany Triyanthi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
This study investigates the antibacterial activity of Moringa oleifera leaf extract against Staphylococcus aureus ATCC 25923, focusing on the effects of harvest time and extract concentration. Leaves were harvested in the morning (08:00–10:00) and afternoon (15:00–17:00), then extracted with 96% ethanol. The antibacterial efficacy was evaluated using the Kirby-Bauer disc diffusion method at 60%, 70%, and 80%. The largest inhibition zone was observed at 80% concentration from the afternoon harvest (10.38 ± 0.43 mm), while the smallest was recorded at 60% from the morning harvest (8.25 ± 0.20 mm). Statistical analysis confirmed a significant concentration‑dependent antibacterial effect (p < 0.001, η² = 88.6%). However, harvest time did not significantly affect inhibition zone size (p = 0.882). These results suggest that M. oleifera is an effective natural antimicrobial agent against S. aureus, with concentration being the key determinant of antibacterial activity. Further research is recommended to explore its potential combined with antibiotics and its full therapeutic applicability.